I Medici: Lorenzo il Magnifico the art of revolution - Fay, John; Sharman, Daniel; James, Bradley; Parish, Sarah 1968- (RAI Cinema, 2019)
In 1470, twenty years after the events told in the first season, Piero and Lucrezia are head of the family. The power of the Medici has consolidated over time, but an attack on Piero's life brings to light years of bad banking management and his eldest son, Lorenzo, is called to take his father's place earlier than expected
Bildformat 16:9
Keywords: Medici, House of / Drama; Medici, Lorenzo de' / 1449-1492 / Drama; Florence (Italy) / History / 1421-1737 / Drama; Television series; Video recordings for the hearing impaired; Film; DVD-Video